Use of provider-to-provider telemedicine in Kenya during the COVID-19 pandemic - Erin J. Kim; Meghan E. Moretti; Antony Mugambi Kimathi; Stephen Y. Chan; Richard Wootton (Frontiers Media S.A., 2022)
IntroductionAccording to the World Health Organization (WHO), about 90 percent of countries continue to report COVID-related disruptions to their health systems. The use of telemedicine has been especially common among high-income countries to safely deliver and access health services where enabling infrastructure like broadband connectivity is more widely available than low- and middle-income countries (LMICs). The Addis Clinic implements a provider-to-provider (P2P) asynchronous telemedicine model in Kenya. We sought to examine the use of the P2P telemedicine platform during the second year of COVID-19.MethodsTo assess sustainability, we compared the data for two 12-month calendar periods (period A = year 2020, and period B = year 2021). To examine performance, we compared the data for two different 12-month periods (period C = pandemic period of February 2021 to January 2022, and period D = baseline period of February 2019 to January 2020).ResultsSustainability of the P2P telemedicine platform was maintained during the pandemic with increased activity levels from 2,604 cases in 2020 to 3,525 cases in 2021. There was an average of 82 specialists and 5.9 coordinators during 2020, and an average of 81 specialists and 6.0 coordinators during 2021. During 2020, there were 444 cases per coordinator, and 587 cases per coordinator in 2021(P = 0.078). During 2020, there were 32 cases per specialist, and 43 cases per specialist in 2021(P = 0.068). Performance decreased with 99 percent of cases flagged as "answered" during the baseline period (period D), and 75 percent of cases flagged as "answered" during the pandemic period (period C).ConclusionResults suggest that despite a decline in certain sustainability and performance indicators, The Addis Clinic was able to sustain a very high level of activity during the second year of the pandemic, as shown by the continued use of the system. Furthermore, despite some of the infrastructure challenges present in LMICs, the P2P telemedicine platform was a viable option for receiving clinical recommendations from medical experts located remotely. As health systems in LMICs grapple with the effects of the pandemic, it is worthwhile to consider the use of telemedicine to deliver essential health services.